Pemanfaatan Panel Surya Untuk Cadangan Daya Pada Proses Fermentasi Bawang Hitam - Pradana, Syaiful; ., solekhan (LPPM Universitas Dharma Andalas, 2025)
The black garlic fermentation process requires a stable power supply to maintain optimal temperature and humidity. However, continuous use of grid electricity increases operational costs. Therefore, this study aims to develop a backup power system using solar panels to reduce reliance on PLN electricity and improve fermentation efficiency. The method used in this study includes designing and implementing a solar panel-based alternative energy system, combined with batteries as energy storage. An automatic control system was developed using Arduino Mega and ESP32, which receives data from ACS712, PZEM004T, and voltage sensors to determine the power source. The monitoring data is displayed via an LCD and accessed in real-time using the Firebase platform and MIT App Inventor. The test results indicate that the system can effectively switch from grid power to solar panels based on detected voltage conditions. By implementing this system, electricity consumption from PLN can be significantly reduced, while solar power can be optimally utilized to sustain the black garlic fermentation process.